Screening and Characterization of Potential Antioxidant Probiotics Isolated from the Gut of Hybrid Grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Zhang, Qian; Cai, Yan; Chen, Zihan; Shi, Huizhong; Zhou, Yongcan; Yang, Yang; Tu, Rui; Chen, Guisen; Wang, Shifeng (Frontiers in Marine Science, 2022)
Some symbiotic probiotics have antioxidant activities and could improve the antioxidant capacity of the host. There is still no report on the screening of host-derived antioxidant probiotics for grouper farming. In this study, 369 out of 583 isolates were screened from the gut of hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus♂) based on their non-hemolytic characteristics. Subsequent preliminary screening with 2,2-Diphenyl-1-Picrylhydrazyl (DPPH) scavenging rate assay resulted in 36 potential antioxidant isolates. After comprehensive evaluation with nine different antioxidant assays (DPPH scavenging rate, 2,2’-azino-bis (3-ethylbezothiazoline)-6-sulfonic acid radical scavenging rate, iron ion reducing ability, reducing activity, O2-· scavenging rate,·OH scavenging rate, ferrous ion chelating rate, hydrogen peroxide tolerance, oxygen-free radical scavenging ability, et al.), 10 isolates with strong antioxidant abilities were screened from 36 potential antioxidant isolates. Then some other probiotic properties, such as simulated gastrointestinal fluid tolerance, adhesion, digestive enzyme activity, and antibacterial activity of the 10 selected isolates were evaluated. All 10 isolates were also identified using the molecular method. Finally, Vibrio rhodolitus GO 91 and Shewanella corallii GO 310, as representatives of the two genera resulting from the identification of the 10 isolates, and with the best overall probiotic properties, were selected from the 10 isolates. Isolates GO 91 and GO 310 were further tested for their safety performances. Antibiotic sensitivity tests showed that GO91 and GO310 were sensitive to many commonly used aquaculture antibiotics. The in vivo challenge test of GO 91 and GO 310 didn’t cause any disease symptoms or death in hybrid grouper. Therefore, isolates GO 91 and GO 310 showed great potential to be used as probiotics in hybrid grouper farming.